2022
DOI: 10.1039/d1cb00103e
|View full text |Cite
|
Sign up to set email alerts
|

Chemoproteomic-enabled characterization of small GTPase Rab1a as a target of an N-arylbenzimidazole ligand's rescue of Parkinson's-associated cell toxicity

Abstract: The development of phenotypic models of Parkinson's disease (PD) has enabled screening and identification of phenotypically active small molecules that restore complex biological pathways affected by PD toxicity.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 81 publications
0
5
0
Order By: Relevance
“…Because activation of both Rab1A and Rab1B were implicated in multiple cancer types ( Yang et al, 2016 ), both should be considered when studying cancer. In contrast, only Rab1A, and not Rab1B, has been associated with neurological disorders, for example, Parkinson’s disease ( Winslow et al, 2010 ; Coune et al, 2011 ; Ejlerskov et al, 2013 ; Mazzulli et al, 2016 ; Hatstat et al, 2022 ), Alzheimer’s disease ( Mohamed et al, 2017 ), amyotrophic lateral sclerosis ( Webster et al, 2018 ), and intellectual disability ( Tabata et al, 2022 ). In light of the results presented here, we propose that it is the function of Rab1A in autophagy that is important for its role in neurological disorders.…”
Section: Discussionmentioning
confidence: 99%
“…Because activation of both Rab1A and Rab1B were implicated in multiple cancer types ( Yang et al, 2016 ), both should be considered when studying cancer. In contrast, only Rab1A, and not Rab1B, has been associated with neurological disorders, for example, Parkinson’s disease ( Winslow et al, 2010 ; Coune et al, 2011 ; Ejlerskov et al, 2013 ; Mazzulli et al, 2016 ; Hatstat et al, 2022 ), Alzheimer’s disease ( Mohamed et al, 2017 ), amyotrophic lateral sclerosis ( Webster et al, 2018 ), and intellectual disability ( Tabata et al, 2022 ). In light of the results presented here, we propose that it is the function of Rab1A in autophagy that is important for its role in neurological disorders.…”
Section: Discussionmentioning
confidence: 99%
“… 356 NAB2 (N-arylbenzimidazole) was identified to alleviate α-Synuclein induced toxicity in PD cell models, and a following chemoproteomic study reveals that RAB1 is a target of NAB2 for its rescuing effects. 357 Exploring the allosteric pockets on the Rab protein surfaces has also been pursued based on structure-based computational analysis. 358 , 359 Relative to other families, drug discovery efforts toward Ran are limited, though there have been some early attempts to interfere with RAN-GEF interactions.…”
Section: Targeting Small Gtpases In Human Diseasesmentioning
confidence: 99%
“…The TPP, CPP, SPROX, PP, LiP, and DART techniques have been most widely used in protein target discovery efforts where the goal is to identify the protein targets of a test ligand. An increasing number of successes using these methods to identify protein targets of drugs , and other biologically relevant molecules ,, have been reported by us and others. In these protein target discovery studies, there is typically much overlap in the protein targets identified using each technique, and it has been noted in some reports that using a combination of these strategies can help differentiate true positives from false positives. ,,, A recent comparative analysis of the analytical capabilities of SPROX, TPP, CPP, and PP using the well-studied ligand, cyclosporine A (CSA), and yeast cell lysate showed the benefits of using all four strategies, the biggest one of which is that the false positive rate can be reduced from 30 to 70% to near 0% if selected protein hits are required to appear in at least two different techniques.…”
Section: Introductionmentioning
confidence: 99%
“…In these protein target discovery studies, there is typically much overlap in the protein targets identified using each technique, and it has been noted in some reports that using a combination of these strategies can help differentiate true positives from false positives. 14,24,28,29 A recent comparative analysis of the analytical capabilities of SPROX, TPP, CPP, and PP using the well-studied ligand, cyclosporine A (CSA), and yeast cell lysate showed the benefits of using all four strategies, 28 the biggest one of which is that the false positive rate can be reduced from 30 to 70% to near 0% if selected protein hits are required to appear in at least two different techniques.…”
Section: ■ Introductionmentioning
confidence: 99%